HUBUNGAN SPASIAL TRANSAKSI TANAH DENGAN PERKEMBANGAN WILAYAH DI KABUPATEN CIREBON, JAWA BARAT - Amin Marzuki; Santun Risma Pandapotan Sitorus; Soekmana Soma (TATALOKA, 2019)
The big potential of Cirebon Regency with good transportation access and demography bonus is able to promote its regional development. Not all of the potential has been optimized to invite investment in Cirebon Regency. One of the causes is some of the lands haven't been registered, so that obstructs investment that requires land. We explore the spatial relationship between the regional development level and land transaction pattern. We calculate the entropy diversification index to see the level of regional development. We also interpolate the land transaction to see the spatial pattern. The natural neighbor interpolation method was used to show spatial patterns of land transactions. Then, we overlay the map of the entropy index and land transaction pattern map to see the relationship spatially. Land transactions in Cirebon Regency gathered in a very developed and developing region. Districts of Palimanan, Depok, Plumbon, Weru, and Plered that are categorized very developed have more quantity of transactions and land transaction value than the undeveloped area. Pasaleman district has Kecamatan Depok, has the smallest entropy index, and categorized as undeveloped has a lower number and value of land transactions. We found a similar spatial pattern between the regional level of development and land transaction interpolation.